Strategies for Constructing College Students' Entrepreneurial Value Judgments Based on Educational Psychology - Chen, Zhen; Yang, Zimo; Li, Yuzhen; Liu, Yuanbing; Jia, Xueling; Gao, Jianhao (Frontiers in Psychology, 2021)
Against the background of economic globalization, the strategies for constructing college students’ entrepreneurial value judgment are explored, providing college graduates with more employment options and thereby keeping up with the trend of the times. The documentary analysis and questionnaire survey methods are adopted to investigate contemporary college students’ entrepreneurial value judgments, and the investigation results are organized. According to documentary materials, the discovered problems are analyzed to put forward strategies for constructing college students’ entrepreneurial value judgments based on educational psychology. Results show that only 14.1% of college graduates choose to start a business; 48.7% do not understand or recognize the entrepreneurial values; 14.8% believe teaching activities on constructing entrepreneurial value judgments are insufficient, and the entrepreneurial atmosphere is lacking. Regarding the above investigation results, strategies for constructing college students’ entrepreneurial value judgments are proposed, involving the construction environment, construction system, construction method, and construction mechanism. Hence, considering contemporary college students’ entrepreneurial values, the proposed strategies for constructing college students’ entrepreneurial judgments are suitable and valuable, providing a practical reference for enriching and perfecting the college innovation and entrepreneurship education systems.